A IMPORTÂNCIA DA MATEMÁTICA FINANCEIRA NO ENSINO MÉDIO E SUA CONTRIBUIÇÃO PARA A CONSTRUÇÃO DA EDUCAÇÃO FINANCEIRA NO CIDADÃO - Gallas, Rafael Guilherme (2013)
The Mathematics Finance have great importance for the high school student, it is in this stage of life that this student enters the work force and start using cash more often. Therefore, this study aims to reinforce the importance of teaching students of Mathematics Finance at the high school, as well as the benefits of its correct use in adulthood. Initially we reviewed the official guidelines such as: PCN, PCNEM and Curricular Guidelines regarding Mathematics Finance later we analyzed some of the textbooks that are used in state schools of the State of Parana to verify if they are in accordance with the guidelines set out in official documents. We propose to review the main concepts of Mathematics Finance used in high school and to developed an activity involving its main concepts. This activity aims to approach the Mathematics Finance in a easier form, based mainly on examples and materials that are close to the students like grocery flyers, involving the social context in which they are inserted as a way to encourage their study and a consequent class improvement , with a possible reduction of class detachment